Reduced computational cost in the calculation of worst case response time for real time systems - Urriza, José M. (2009)
Modern Real Time Operating Systems require reducing computational costs even though the microprocessors become more powerful each day. It is usual that Real Time Operating Systems for embedded systems have advance features to administrate the resources of the applications that they support. In order to guarantee either the schedulability of the system or the schedulability of a new task in a dynamic Real Time System, it is necessary to know the Worst Case Response Time of the Real Time tasks during runtime. In this paper a reduced computational cost algorithm is proposed to determine the Worst Case Response Time of Real Time tasks.Modern Real Time Operating Systems require reducing computational costs even though the microprocessors become more powerful each day. It is usual that Real Time Operating Systems for embedded systems have advance features to administrate the resources of the applications that they support. In order to guarantee either the schedulability of the system or the schedulability of a new task in a dynamic Real Time System, it is necessary to know the Worst Case Response Time of the Real Time tasks during runtime. In this paper a reduced computational cost algorithm is proposed to determine the Worst Case Response Time of Real Time tasks.